Sample-based longitudinal discrete choice experiments: preferences for electric vehicles over time - Katharina Keller; Christian Schlereth; Oliver Hinz (Journal of the Academy of Marketing Science, 2021)
Discrete choice experiments have emerged as the state-of-the-art method for measuring preferences, but they are mostly used in cross-sectional studies. In seeking to make them applicable for longitudinal studies, our study addresses two common challenges: working with different respondents and handling altering attributes. We propose a sample-based longitudinal discrete choice experiment in combination with a covariate-extended hierarchical Bayes logit estimator that allows one to test the statistical significance of changes. We showcase this method's use in studies about preferences for electric vehicles over six years and empirically observe that preferences develop in an unpredictable, non-monotonous way. We also find that inspecting only the absolute differences in preferences between samples may result in misleading inferences. Moreover, surveying a new sample produced similar results as asking the same sample of respondents over time. Finally, we experimentally test how adding or removing an attribute affects preferences for the other attributes.
Keywords: 330; Adoption; Electric vehicles; Complementary mobility services; Discrete choice experiment; Dual response; Sample-based longitudinal study